Banished men: how migrants endure the violence of deportation - Andrews, Abigail (University of California Press, 2023)
"What becomes of men the US locks up and kicks out? From 2009 to 2020, the US deported more than five million people-over 90 percent of them men. Banished Men tells 186 of their stories. How, it asks, does forced expulsion shape men's lives and sense of themselves? In this book, a team of thirty-one Latinx students and an award-winning scholar of gender and migrant exclusion uncover a harrowing system that weaves together policing, prison, detention, removal, and border militarization-and overwhelmingly targets men. Guards and gangs beat them down, both literally and metaphorically, as if they are no more than vermin or livestock. Their ties with family are severed. In Mexico, they end up banished: in limbo and stripped of humanity. They do not go "home." Their fight for new ways of belonging, as people of both "here" and "there," forms a devastating, humane, and clear-eyed critique of the violence of deportation"--